A global analysis of self-sufficiency and diversity displays diverse supply risks - Wassénius, Emmy (Stockholm University, 2022)
To understand the diverse risk landscape that affects national food supply it is important to understand the food self-sufficiency and diversity of (national) domestic food production. This is a novel dataset on national food production covering all food sectors (both terrestrial and aquatic), providing data on the production of both macro and micronutrient compositions. The dataset consists of three files: 1) A READ_ME file providing metadata information for the other two files. 2) A file called nutrient_production.csv providing the production (in nutritional composition) of each food item per country and year. 3) A file called item_ID_list.csv which provides information on what each item ID in the nutrient_production file refers to.
In the associated article this dataset is used to highlight the diverse risks that come from lack of self-sufficiency and a lack of diversity.
The dataset can also be explored through the interactive online tool: https://emmywas.shinyapps.io/food_supply_risks/ All R code for the analysis and production of the online tool can be found at: https://github.com/emmywas/food_supply_risks

R, 4.1.2
Keywords: Earth and Environmental Sciences; Food production; Diversity; Nutritional composition; Nutrient composition and food production data; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap